Kehidupan Sosial Ekonomi Masyarakat Suku Duano di Kelurahan Tanjung Solok Kabupaten Tanjung Jabung Timur Tahun 2012-2020 - Iza Sapitri; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2022)
This study discusses the Socio-Economic Life of the Duano Tribe Community in Tanjung Solok Village, Tanjung Jabung Timur Regency and the role of the government in advancing the economy of the Suano Tribe community. The purpose of this study is to describe the socio-economic conditions of the Duano Tribe community, such as livelihood, culture, language, education, religion and to explain the extent to which the government's role in advancing the economy of the Duano Tribe community is. This research includes historical qualitative research using historical methods in the form of interviews, archive studies, and literature studies. From the discussion, it can be seen that, (1) the Duano Tribe is a society whose life depends on nature. The Duano people usually live in coastal areas so that their livelihood is as fishermen. In interacting, the Duano people use Malay as the majority used in Tanjung Solok Village. The unique tradition of the Duano Tribe is to catch or pluck the axis. (2) there are several government efforts in advancing the economy of the Duano Tribe community, such as the Samudra Program and the Five Year Program given by the government to the Duano Tribe fishermen. The assistance is in the form of Pompong or armpits, fishing gear and house repairs. Keywords: Duano Tribe, Socio-Economic, Government